7th International Munich Chassis Symposium 2016 chassis.tech plus - Pfeffer, Prof. Dr. Peter E.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2017)
In chassis development, the three aspects of safety, vehicle dynamics and ride comfort are at the top of the list of challenges to be faced. Addressing this triad of challenges becomes even more complex when the chassis is required to interact with assistance systems and other systems for fully automated driving. What is more, new demands are created by the introduction of modern electric and electronic architectures. All these requirements must be met by the chassis, together with its subsystems, the steering, brakes, tires and wheels. At the same time, all physical relationships and interactions have to be taken into account. Contents New chassis systems.- New chassis systems and methods.- Simulation.- Vehicle handling optimization and control.- Chassis architectures.- Simulators.- Highly automated driving.- Functional safety.- Brake development methods.- Future brake systems and technologies.- Tire technology and trends.- Components of the chassis.- Steering feel and steer-by-wire.- New requirements and solutions in brake development.- Future technology. Target audiences Automotive engineers and chassis specialists as well as students looking for state-of-the-art information regarding their field of activity - Lecturers and instructors at universities and universities of applied sciences with the main subject of automotive engineering - Experts, researchers and development engineers of the automotive and the supplying industry Publisher ATZ live stands for top quality and a high level of specialist information and is part of the worldwide specialist scientific publishing group Springer Science + Business Media. Partner TÜV SÜD is an international leading technical service organisation catering to the Industry, Mobility and Certification Segment.
New chassis systems -- New chassis systems and methods -- Simulation -- Vehicle handling optimization and control -- Chassis architectures -- Simulators -- Highly automated driving -- Functional safety -- Brake development methods -- Future brake systems and technologies -- Tire technology and trends -- Components of the chassis -- Steering feel and steer-by-wire -- New requirements and solutions in brake development -- Future technology.
Keywords: Automotive engineering; Engines; Automotive Engineering; Engine Technology